PENGARUH GAYA KEPEMIMPINAN DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA LATTERIA GELATO JAKRTA BARAT - Misel Amelia Putri; Nurdinni Tilova (Jurnal Menara, 2026)
This study aims to analyze the influence of Leadership Style and Teamwork on Employee Performance at Latteria Gelato, both partially and simultaneously. The research uses a descriptive quantitative method with 46 respondents selected through purposive sampling. The results of the regression analysis show that Leadership Style partially has a significant effect on Employee Performance, as indicated by the regression equation Y = 4.132 + 0.478 X1 and an R Square value of 0.612 (61.2% of the variation is explained by Leadership Style). The partial t-test for Leadership Style shows a t-count of 5.736 > t-table of 2.017 and a significance value of 0.000 < 0.05, so H₀ is rejected and Hₐ is accepted. Likewise, Teamwork also has a significant partial effect on Employee Performance, with the regression equation Y = 3.892 + 0.529 X2 and an R Square value of 0.645. The t-count for Teamwork is 6.104 > t-table and the significance value is 0.000 < 0.05, indicating H₀ is rejected and Hₐ is accepted. Simultaneously, Leadership Style and Teamwork significantly influence Employee Performance, as shown by the regression equation Y = 2.987 + 0.311 X1 + 0.402 X2 and an R Square value of 0.721. The F-test yields an F-count of 54.789 > F-table of 3.21 with a significance value of 0.000 < 0.05, confirming that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that both Leadership Style and Teamwork simultaneously have a significant effect on Employee Performance at Latteria Gelato.